L’initiation. Entretien avec un client de la prostitution - Sébastien Roux (Genre, Sexualité et Société)
Few studies on sex work concentrate on male clients. It might be understood as the result of both (1) methodological difficulties and (2) the moral condemnation of prostitution that explains why sex work analyses will focus on offer rather than demand. However, by publishing extracts from an in-depth interview conducted with Damien – a French young expatriate met in Bangkok during a fieldwork on ‘sex tourism’ – I suggest that prostitution is a complex process, too often reduced to an univocal relation of domination. Damien describes his first experience of prostitution as a client, explaining uncertainties and negotiations that characterize commercial sex. But rather than analyzing male demand for prostitution as a form of essentialized deviance, I propose to consider Damien’s discourse as relevant to understand how the social and historical contexts transform prostitutional relations.